1997
DOI: 10.1046/j.1464-410x.1997.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urinary CD14 after intravesical bacille Calmette‐Guérin immunotherapy for carcinoma in situ

Abstract: Objective To characterize the production of the monoalthough in most patients there was a minor band of reactivity at 54 kDa. A panel of human bladder cancer cyte activation marker, soluble CD14 (sCD14), after bacille Calmette-Guérin (BCG) immunotherapy for cell lines did not react with the anti-CD14 monoclonal antibodies 3C10, 5C5 and BA8, and the antibodies superficial bladder cancer. Patients and methods Nineteen patients with carcinoma also failed to react with malignant epithelial cells in frozen sections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The adjuvant administered to both experimental and control groups, however, contained Mycobacterium bovis, which is well known to produce both strong humoral and cellular immune responses. [21][22][23][24][25] Indeed, we found equivalent levels of anti-Mycobacterium antibodies in the plasma of animals from all groups. We consider it unlikely that the immune responses to PDGF-AA, platelet proteins, and saline (other than the specific activity of the antibodies) differentially effected atherogenesis in the 3 groups against the background of the immune response to Mycobacterium bovis.…”
Section: The Importance Of Immunomodulation In Atherosclerosissupporting
confidence: 50%
“…The adjuvant administered to both experimental and control groups, however, contained Mycobacterium bovis, which is well known to produce both strong humoral and cellular immune responses. [21][22][23][24][25] Indeed, we found equivalent levels of anti-Mycobacterium antibodies in the plasma of animals from all groups. We consider it unlikely that the immune responses to PDGF-AA, platelet proteins, and saline (other than the specific activity of the antibodies) differentially effected atherogenesis in the 3 groups against the background of the immune response to Mycobacterium bovis.…”
Section: The Importance Of Immunomodulation In Atherosclerosissupporting
confidence: 50%
“…Several investigators have studied cytokine secretion in response to BCG instillation. Jackson et al [18] showed that the urine levels of soluble CD14 is significantly higher in patients responding to BCG therapy as compared with nonresponders. In a small study on 20 patients receiving BCG treatment for superficial bladder cancer, Thalmann et al [16] observed that only 1 of 10 patients with urinary IL-8 concentrations Ͼ4 g/l 6 h after BCG instillation had a tumor recurrence, while all patients with urinary soluble CD14 concentrations Ͻ4 g/l subsequently developed a tumor recurrence.…”
Section: Bcg Treatment Of Superficial Bladder Cancer: Open Questionsmentioning
confidence: 99%
“…Increases of interleukin (IL)1ß, IL-2 [1214], IL-8 [15,16], interferon gamma (IFN-␥) [17], tumor necrosis factor alpha (TNF-␣), and soluble CD14 [18], a monocyte activation marker, have been reported. The secretion of these factors clearly demonstrates the presence of an immune reaction, and, furthermore, there is some evidence that the intensity of this secretion can even be linked with the response to BCG treatment.…”
Section: Introductionmentioning
confidence: 99%